2014
DOI: 10.1007/s10695-014-9912-0
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic development of digestive functionality in golden pompano Trachinotus ovatus (Linnaeus 1758)

Abstract: Ontogenetic development of the digestive system in golden pompano (Trachinotus ovatus, Linnaeus 1758) larvae was histologically and enzymatically studied from hatch to 32 day post-hatch (DPH). The development of digestive system in golden pompano can be divided into three phases: phase I starting from hatching and ending at the onset of exogenous feeding; phase II starting from first feeding (3 DPH) and finishing at the formation of gastric glands; and phase III starting from the appearance of gastric glands o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
38
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 32 publications
13
38
0
Order By: Relevance
“…Both amylase and lipase specific activities were detected as early as 1 DAH, suggesting that these enzymes were also genetically pre-programmed as reported in some other fish species (Cuvier-Péres and Lazo et al 2007;Martínez-Lagos et al 2014;Ma et al 2014). The amylase specific activity around 5 DAH was low coincided with the initial feeding, suggesting the poor ability of Chinese loach to utilize carbohydrates at mouth opening (4 DAH).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Both amylase and lipase specific activities were detected as early as 1 DAH, suggesting that these enzymes were also genetically pre-programmed as reported in some other fish species (Cuvier-Péres and Lazo et al 2007;Martínez-Lagos et al 2014;Ma et al 2014). The amylase specific activity around 5 DAH was low coincided with the initial feeding, suggesting the poor ability of Chinese loach to utilize carbohydrates at mouth opening (4 DAH).…”
Section: Discussionsupporting
confidence: 59%
“…It may be associated with the transition from endogenous to exogenous feeding (Oozeki and Bailey 1995). After 30 DAH, the significant increase in lipase specific activity coincides with weaning to a compound diet (30 DAH), and similar pattern is also observed in spotted rose snapper (Lutjanus guttatus) (Moguel-Hernández et al 2014) and golden pompano (Trachinotus ovatus) (Ma et al 2014), suggesting that the lipase activity may be strongly influenced by the type of diet and dietary lipid level.…”
Section: Discussionsupporting
confidence: 55%
“…Although there has been some debate as to whether amylase production coincides with mouth Fish Physiol Biochem opening or is produced shortly thereafter (Suzer et al 2006;Tong et al 2012;Ma et al 2014b), it is likely that the observed variation is a result of genetic factors and species-species differences. In American shad larvae, specific amylase activity was observed at hatching and increased sharply from 3 DAH until 10 DAH, which indicated that the larvae have the ability to digest carbohydrates during the early stages.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature can regulate fish metabolism, food intake and growth (Jobling 1994; Ma 2014), and the effects of temperature on fish growth have been well documented in the larvae of commercially important fish species including haddock Melanogrammus aeglefinus L. (Martell et al 2005), nase Chondrostoma nasus L. (Keckeis et al 2001), Australian snapper Pagrus auratus (Fielder et al 2005), striped trumpeter Latris lineata (Choa et al 2010), and yellowtail kingfish Seriola lalandi (Ma 2014). In golden pompano, the fast growth at high temperature may be attributed to the improved food ingestion and digestive function of fish larvae after 15 DPH as Ma et al (2014b) reported that the goblet cells and gastric glands appeared in the gut of golden pompano larvae after 15 DPH at 27–29 °C. The growth of fish larvae tended to be accelerated when fish were weaned from rotifers to Artemia nauplii.…”
Section: Discussionmentioning
confidence: 99%
“…Although the early ontogenetic development of digestive functionality (Ma et al 2014a, b) and weaning strategies have been studied on golden pompano (Ma et al 2014d), high jaw malformation during the early developmental stages has severely compromised production efficiency of this fish species in hatcheries. Our previous studies have identified the type, position, and frequency of jaw and skeletal malformations in golden pompano larvae (Ma et al 2014c; Zheng et al 2014), but factors causing skeletal malformation on this fish have never been evaluated.…”
Section: Introductionmentioning
confidence: 99%